Efficient Market Hypothesis in Emerging Market - a Conceptual Analysis - Kofarbai, Hamza Zubairu; Zubairu, Muhammad (European Scientific Journal, ESJ, 2016)
The aim of this paper is to explain the importance and implications of the use of Efficient Market Hypothesis (EMH) in emerging market with a view to see how portfolio assets are priced and the rationale behind it. The EMH describes a rational market where all relevant available information is reflected very quickly on prices. In an efficient market prices should react only to new unanticipated information, and since this is unpredictable, by definition, price changes must be unpredictable also. The EMH describes the case of an ideal stock market where actual prices fully reflect all relevant information. Consequently, the price and corresponding return fluctuations are not predictable and it's impossible for investors to make gains systematically. For many years, the EMH seemed to describe adequately the price behaviour in the world stock markets. Nevertheless, recent finding indicates otherwise. The research design of the paper is qualitative and content analysis is going to be use. The paper concludes that despite its shortcoming the EMH remains an open issue and it has help in deepening stock markets worldwide because of it acceptability. Therefore the paper recommends that more researchers should be encouraged to be conducted in emerging market of Africa especially that of Nigeria.